Cultural differences of lifelong learners in using emerging technologies - PEI-WEI LEE (Adult Education Research Conference, 2016)
To examine emerging technologies and discuss their potential to improve teaching and learning with respect to cultural factors. Understanding the cultural differences and how they affect teaching and learning will inform higher education to offer a friendly environment that benefit adult learners.
Keywords: emerging technologies; cultural differences; lifelong learners